Rifaximin induces and maintains clinical remission in a dachshund with chronic enteropathy: antibiotic‐responsive diarrhoea or inflammatory bowel disease?. Issue 1 (16th May 2017) - Menozzi, Alessandro; Dall'Aglio, Manuel; Quintavalla, Fausto; Meucci, Valentina; Bertini, Simone
Abstract : A two‐year‐old male dachshund was presented with a long‐term history of chronic small intestine diarrhoea. The dog had been previously treated with several antibiotics, with temporary remission of clinical signs, relapsing each time the therapy was discontinued. On the basis of clinical signs, history and on the investigations performed which failed to detect any other cause of disease, a diagnosis of antibiotic‐responsive diarrhoea (ARD) or small intestine bacterial overgrowth secondary to inflammatory bowel disease was made. A three‐week antibiotic treatment with rifaximin by oral route was prescribed, achieving a prompt clinical remission but diarrhoea relapsed shortly after the end of drug administration. A continuous therapy with rifaximin was therefore established, allowing to maintain the dog in complete remission, without any side effect. The efficacy shown by rifaximin in this report suggests, for the first time, that this drug could be a good choice for long‐term treatment of ARD.